PENENTUAN NILAI KOEFISIEN TANAMAN DARI BEBERAPA SPESIES TANAMAN HORTIKULTURA PADA TANAH INCEPTISOL DENGAN PEMBENAH KOMPOS (Determination of The Value of Crop Coefficients of Several Species of Horticultural Plant on Inceptisol Soil by Composting) - Nurul Tri Rahmadani; Sumono Sumono; Delima Lailan Sari Nasution (Jurnal Rekayasa Pangan dan Pertanian, 2018)
ABSTRACT   The evapotranspiration value of plant can be determined based on the potential evaporation value and the crop coefficient for each species from its growth period. The objective of this research is to determine the crop coefficient values of Pakcoy (Brassica rapa L.), Caisim (Brassica juncea L.), and Lettuce (Lactuca sativa L.) on Inceptisol soil with the addition of compost. The results showed that the soil texture of each planting medium was sandy loam, with the ranges of organic materials content of 5.89-6.25%, the ranges of porosity were 52.95-53.87-%, moisture capacity for each plants (Pakcoy, Caisim, and Lettuce) were 46.46%, 44.31%, and 47.87%, dry weight of each plants (Pakcoy, Caisim, and Lettuce) were 75 gr, 85 gr, and 35 gr, and then the value of the crop coefficient for Pakcoy, Caisim and Lettuce in the middle period of growth (16-30 days) were 0.44; 0.60 and 0.50. As well as the value of the crop coefficient of Pakcoy, Caisim and Lettuce in the final phase of growth (31-45 days) were 0.30; 0.31 and 0.44.   Keywords: Crop coefficient of plants, pakcoy, caisim, lettuce, inceptisol, compost. ABSTRAK Nilai evapotranspirasi tanaman dapat ditentukan berdasarkan nilai evaporasi potensial dan koefisien tanaman untuk setiap spesies tanaman dari periode pertumbuhannya. Penelitian ini bertujuan untuk menentukan nilai koefisien beberapa tanaman Pakcoy (Brassica rapa L.), Caisim (Brassica  juncea L.), dan Selada (Lactuca sativa L.)  pada tanah Inceptisol dengan pembenahan kompos. Hasil penelitian menunjukkan untuk masing-masing media tanam, tekstur tanah berupa lempung berpasir dengan kandungan bahan organik berkisar 5,89- 6,25%, porositas berkisar 52,95-53,87%, kadar air kapasitas lapang untuk tanaman Pakcoy, Caisim dan Selada masing-masing sebesar 46,46%, 44,31% dan 47,87%, berat kering tanaman untuk tanaman Pakcoy, Caisim dan Selada pada fase akhir (31-45 hari) masing-masing sebesar 75 gr, 85 gr, dan 35 gr, nilai koefisien tanaman Pakcoy, Caisim dan Selada pada periode tengah pertumbuhan (16-30 hari) berturut-turut sebesar 0,44; 0,60 dan 0,50 serta pada fase akhir pertumbuhan (31-45hari) berturut-turut sebesar 0,30; 0,31 dan 0,44.   Kata Kunci: Koefisien tanaman, pakcoy,  caisim, selada, inceptisol, kompos.